Peran Guru Pendidikan Agama Islam: Peningkatan Hermeneutika Materi Pembelajaran Pada Siswa Sekolah Dasar - Adiyono, Adiyono; Rusdi, Muhammad; Sara, Yuni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
In general, Islamic Religious Education is an education that leads and teaches the values of Islam and its main target is students who are studying both formal, non-formal and informal education. The importance of the role of PAI teachers to achieve the learning objectives of Islamic Religion which creates intellectual students not only in the field of general knowledge but also in the field of Islamic education. Making PAI teachers have a moral and professional responsibility in improving the hermeneutics of learning materials for students. In this case we want to discuss the role of PAI teachers on the hemeneutics of learning materials at SDIT Al Khawarizmi Tanah Grogot. How to improve hemeneutics in students towards material in the management of learning implemented by educators, especially in Islamic Religious Education learning. This research method uses interviews with several students and PAI teachers. The results of this study want to show that the efforts of PAI teachers in improving the hermeneutics of learning materials in SDIT Alkhawarizmi students are very good.